Heat treatment, selection, and application of tool steels - Bryson, William E. (Hanser Gardner Publications, 2005)
In a few short years, this has become the established reference for tool makers, heat treaters, and engineers seeking step-by-step recipes for properly heat treating a wide range of tool steels, plus practical information about machinability, shock resistance, wear, and extending tool life. Now, the completely revised and expanded second edition of this best-selling title is available. It has been extensively updated and includes the following significant additions: an entirely new chapter on the popular powdered tool steel CPM 10V; a thorough section on carburizing thoroughly describes the process and its benefits; a section on cryogenic treatment which has been completely rewritten to describe the theory and process; and a comprehensive glossary of related terms. As in the first edition, valuable tables of properties, attributes, qualities and shortcomings of popular tool steels are also included.
Includes index.
Keywords: Tool-steel.; Tool-steel -- Heat treatment.; elektronické knihy; electronic books